Influência das dimensões da empresa familiar na capacidade de absorção dos gestores-proprietários e as implicações na exploratory innovation e exploitative innovation - Santos, Nadiesca Manica dos (2020)
The main theme of the dissertation is the individual absorptive capacity in the context of family businesses, in which the dimensions of the family business (family structure, family functions, family events and the relationship between family members) and the implications for exploratory innovation and exploitative innovation of the company. The general objective of the study was to understand the influence of the dimensions of the family business on the absorption capacity of the proprietary managers and the implication in the company's exploratory innovation and exploitative innovation”. Specifically, it was necessary to identify and describe the positions and functions of the members of the company and categorize them into family members and non-family members, describe the roles that each one plays in organizational management, considering their family role and the dimensions of the individual absorption capacity, assess the roles played by family members in the company and categorize them into gatekeeper, shepherds or “other”, and assess their involvement in the company's exploratory innovation and exploitative innovation. The theoretical argument is that the individual absorptive capacity precedes the organizational, since it is necessary to understand the role of individuals in the capacity of companies to absorb external knowledge. Such a theoretical conception shifts the debate about absorptive capacity from the organizational level to the individual and places the specificities of family businesses at the center of the debate. Due to the influence of the owning family in the management of the family business, the roles of gatekeepers and shepherds assumed by the owner-managers in the absorption capacity, change and influence the company's exploratory innovation and exploitative innovation. It is configured in an applied social research developed at the descriptive level, guided by the multiple case study strategy, with a qualitative approach, whose scientificity is theoretically proven. The method used was content analysis and the techniques were categorical and structural analysis. The perspective of analysis is interpretative and takes place under the theoretical foundations of the individual absorption capacity and the specificities of the family business. This study resulted in the finding that the dimensions of ACAP are directly associated with individual learning capacities, that is, the ability to identify external knowledge, assimilate it and apply it with a view to innovation in the company. Studies on individual ACAP, when carried out in family businesses, need to consider, in addition to the basic skills and previous experiences of engaged individuals, which Cohen and Levinthal (1990) suggest, the trust relationships between employees and managers who behave similarly to family members and / or to members of the owner family with the longest experience in the company, which is 11 generally long. The evidence proves that in the three dimensions of the individual ACAP, the dynamics of the family business (family structure, family functions, family events and the relationship between family members) influence and change the roles assumed in the absorption of knowledge, mainly implying in the exploitative innovation of company. In family businesses, owner-managers are seen as facilitators of innovative actions observed through the parts that make up the individual ACAP process. The family structure determines the functions that each member of the family, or equivalent to it, assumes, therefore the family's decisions influence those who seek knowledge, how this is assimilated internally and applied so that it results in the company's exploratory innovation and exploitative innovation.